"Even in the most insignificant publication, there must be plan and order": On natural history as a theme and genre in Danish-Norwegian parish topographies of the late eighte enth century. Issue 3 (September 2021) - Mellemgaard, Signe
Highlights: Between 1750 and 1820, a large quantity of 'oeconomic-physical' descriptions of Danish- Norwegian parishes appeared. Natural history had a central role in these—both as an object of the enquiry and as a model for it. They also provided "gaps and fissures" that sporadically allowed the practical work of their nature-loving authors to emerge. Abstract: Like the rest of Scandinavia, Denmark and Norway have a strong tradition of comprehensive topographical descriptions, often written by local clergymen. Physical-economic descriptions of small areas, most often parishes, emerging in the middle of the eighteenth century soon formed a model that remained strikingly uniform until around 1820, when the topographies changed once again. In the Dual Monarchy of Denmark and Norway, the years between 1760 and 1820 revealed a prolific topographic genre in which natural history and natural resources played important parts. Natural history was essential, being regarded as the condition for the composite peasant economy and offering the opportunity to reveal unknown sources of livelihood or intensify the use of those sources. Natural history was not only an aspect of the locality that should be dealt with in the description of the locality, but it became an entire scheme or method for the whole description, in which knowledge took up the form of inventories as did natural history itself. The topographical descriptions give hints as to the sort of observing, collecting, identifying, sorting, and ordering practices that lay behind the text. The concise and neutral form of these topographies did not give much room for the emotionality otherwise considered in the period as both a precondition for and an effect of dealings with natural history, and only rarely, in small gaps, did the sensual and aesthetic preferences of the authors come through, occasionally revealing their doubts but also their love of nature.